Cloning, expression and characterization of the gene encoding the enolase from Fusobacterium nucleatum - Mutlu, Özal (My University, 2016)
The gene encoding enolase from Fusobacterium nucleatum (FnENO) was cloned and analyzed for the first time. The gene comprises of 1302 nucleotide base pairs and encodes 433 amino acids. The gene sequence alignment demonstrated the presence of several distinct insertions and deletions, compared with the human enzyme. The gene for recombinant FnENO was inserted into the pLATE 31 vector system and expressed in E. coli BL21(DE3) cells as a soluble protein. The protein was purified by affinity chromatography using a Ni-NTA agarose matrix and shown on SDS-PAGE to be a 46 kDa protein. The molecular weight of the octameric form of the purified recombinant protein was determined as being 375 kDa by size exclusion chromatography. Optimal enzyme activity was observed at pH 8.5 and the enzyme remained stable at a range of different temperatures from 30 to 60°C. Using 2-phosphoglyceric acid as substrate for the purified enzyme, KM, kcat and kcat/KM were determined as 0.48 mM, 20.4 s–1 and 4.22 × 104 M–1s–1, respectively. Potential drug binding sites of FnENO were detected using homology modeling. These data could facilitate the design of new inhibitors of F. nucleatum which has already been shown to be resistant to several known antibiotics. © 2016, Pleiades Publishing, Inc.
Keywords: enolase; Fusobacterium nucleatum; homology modeling; kinetic characterization; periodontal diseases